Low Expression of Stanniocalcin 1 (STC-1) Protein Is Associated With Poor Clinicopathologic Features of Endometrial Cancer - Khatun Masuma; Urpilainen Elina; Ahtikoski Anne; Arffman Riikka K.; Pasanen Annukka; Puistola Ulla; Tapanainen Juha S.; Andersson Leif C.; Butzow Ralf; Loukovaara Mikko; Piltonen Terhi T. (FRONTIERS MEDIA SA, 2025)
Stanniocalcin-1 (STC-1) is a glycoprotein hormone involved in diverse biological processes, including regulation of calcium phosphate homeostasis, cell proliferation, apoptosis, inflammation, oxidative stress responses, and cancer development. The role of STC-1 in endometrial cancer (EC) is yet to be elucidated. In this study, we investigated the protein expression pattern of STC-1 in a tissue microarray (TMA) cohort of hysterectomy specimens from 832 patients with EC. We then evaluated the prognostic value of STC-1 expression regarding the clinicopathologic features and patients survival over a period of 140 months. Our results revealed that in EC tissue samples, STC-1 is mainly localized in the endometrial epithelium, although some expression was also observed in the stroma. Decreased STC-1 expression was associated with factors relating to a worse prognosis, such as grade 3 endometrioid tumors (p = 0.030), deep myometrial invasion (p = 0.003), lymphovascular space invasion (p = 0.050), and large tumor size (p = 0.001). Moreover, STC-1 expression was decreased in tumors obtained from obese women (p = 0.014) and in women with diabetes mellitus type 2 (DMT2; p = 0.001). Interestingly, the data also showed an association between DNA mismatch repair (MMR) deficiency and weak STC-1 expression, specifically in the endometrial epithelium (p = 0.048). No association was observed between STC-1 expression and disease-specific survival. As STC-1 expression was particularly low in cases with obesity and DMT2 in the TMA cohort, we also evaluated the correlation between metformin use and STC-1 expression in an additional EC cohort that only included women with DMT2 (n = 111). The analysis showed no difference in STC-1 expression in either the epithelium or the stroma in women undergoing metformin therapy compared to metformin non-users. Overall, our data may suggest a favorable role for STC-1 in EC behavior; however, further studies are required to elucidate the detailed mechanism and possible applications to cancer treatment.